Depth/Age of changes in ODP Site 121-758 (Table 1) - Christian T Klootwijk; Jeff S Gee; John W Peirce; Guy M Smith (PANGAEA, 1992)
Magnetic susceptibility, remanence and lithostratigraphic profiles for the Neogene-Quaternary sequence at Site 758 (ODP Leg 121) on the northern Ninetyeast Ridge show distinct changes, dated from biostratigraphy and detailed magnetostratigraphy, at 17.5, 10.4-10.0, 8.8, 6.5, 5.4-5.1, 2.7-2.5, 1.9, and 1.2-1.1 Ma. These magnetic and lithologic changes appear to reflect changes in the supply and character of terrigenous material from the Himalayan-Tibetan region resulting from changes in gradient of the Ganges, Brahmaputra and probably the ancient Indus drainage systems. The sedimentary changes can be correlated with changes in uplift-sensitive markers such as the oceanic 87Sr/86Sr ratio and monsoonal induced upwelling, but not clearly so with sealevel variations. We interpret these sedimentary changes, therefore, to primarily reflect changes in the tectonic evolution of the Himalayan-Tibetan region. The changes in the distal marine sedimentary record of the northern Ninetyeast Ridge are compared with isotopic control on the timing of Himalayan-Tibetan tectonic phases and magnetostratigraphic control on their reflection in the proximal Siwalik molasse record. This comparison indicates that the distal Ninetyeast Ridge record can be used to detail and to place minimal age constraints on tectonic phases in the wider Himalayan region and on evolution of the proximal molasse sequence, with a time lag determined for the four earliest changes at less than 1 m.y. The changes at 17.5 Ma and 5.4-5.1 Ma can be interpreted in terms of the causative chain: enhanced plate motion -> uplift and sedimentation change -> climatic change, supporting arguments that the Late Cainozoic global climatic deterioration is driven by uplift of large plateaus such as the Himalayan-Tibetan region and the Western Cordillera.
Supplement to: Klootwijk, CT et al. (1992): Neogene evolution of the Himalayan-Tibetan region: constraints from ODP Site 758, northern Ninetyeast Ridge; bearing on climatic change. Palaeogeography, Palaeoclimatology, Palaeoecology, 95(1-2), 95-110, https://doi.org/10.1016/0031-0182(92)90167-4